Effects of sintering temperatures on the microstructure and mechanical properties of S390 powder metallurgy high-speed steel - Hu, Qipeng; Wang, Miaohui; Chen, Yunbo; Si, Zhen; Zhang, Dongyue (Frontiers in Materials, 2023)
High-performance complex gear cutters and high-temperature bearings are just some of the applications where high-speed steels (HSSs) shine as a preferred material choice owing to their high hardness and outstanding wear resistance. The effects of sintering temperature on the microstructure and mechanical properties of spark plasma sintered (SPS) HSS were investigated in this work. The HSS specimens were prepared via SPS with a range of sintering temperatures from 930 to 1090 °C, a uniaxial pressure of 50 MPa, and a holding time of 5 min. The results demonstrated that the improvements in density, hardness, red hardness, and three-point bending strength were confirmed as the sintering temperature increased from 930 to 1090 °C. Temperature-induced microstructure evolutions were assessed for their contribution to property enhancement, such as powders with varying dimensions and carbides with diverse morphology and diameter. The specimen with the best comprehensive mechanical properties (67.1 HRC and 1196.67 MPa) was prepared at 1050 °C. The wear coefficients decreased as the sintering temperature increased, and the observation results of worn surfaces of test pins confirmed that abrasive wear and oxidation wear dominated the wear experiments. Furthermore, the wear mechanism of dense and porous SPS HSS was illustrated and analyzed in terms of debris and carbides.